Masticatory sensory-motor changes after an experimental chewing test influenced by pain catastrophizing and neck-pain-related disability in patients with headache attributed to temporomandibular disorders - La Touche, Roy (J Headache Pain, 2015)
BACKGROUND: Recent research has shown a relationship of craniomandibular disability with neck-pain-related disability has been shown. However, there is still insufficient information demonstrating the influence of neck pain and disability in the sensory-motor activity in patients with headache attributed to temporomandibular disorders (TMD). The purpose of this study was to investigate the influence of neck-pain-related disability on masticatory sensory-motor variables. METHODS: An experimental case–control study investigated 83 patients with headache attributed to TMD and 39 healthy controls. Patients were grouped according to their scores on the neck disability index (NDI) (mild and moderate neck disability). Initial assessment included the pain catastrophizing scale and the Headache Impact Test-6. The protocol consisted of baseline measurements of pressure pain thresholds (PPT) and pain-free maximum mouth opening (MMO). Individuals were asked to perform the provocation chewing test, and measurements were taken immediately after and 24 hours later. During the test, patients were assessed for subjective feelings of fatigue (VAFS) and pain intensity. RESULTS: VAFS was higher at 6 minutes (mean 51.7; 95% CI: 50.15-53.26) and 24 hours after (21.08; 95% CI: 18.6-23.5) for the group showing moderate neck disability compared with the mild neck disability group (6 minutes, 44.16; 95% CI 42.65-45.67/ 24 hours after, 14.3; 95% CI: 11.9-16.7) and the control group. The analysis shows a decrease in the pain-free MMO only in the group of moderate disability 24 hours after the test. PPTs of the trigeminal region decreased immediately in all groups, whereas at 24 hours, a decrease was observed in only the groups of patients. PPTs of the cervical region decreased in only the group with moderate neck disability 24 hours after the test. The strongest negative correlation was found between pain-free MMO immediately after the test and NDI in both the mild (r = −0.49) and moderate (r = −0.54) neck disability groups. VAFS was predicted by catastrophizing, explaining 17% of the variance in the moderate neck disability group and 12% in the mild neck disability group. CONCLUSION: Neck-pain-related disability and pain catastrophizing have an influence on the sensory-motor variables evaluated in patients with headache attributed to TMD.